Immersive 360° Virtual Reality for Traditional Dance Learning and Preservation in South Sulawesi, Indonesia - Sahnir, Nurachmy; Jamilah, Jamilah; Makawi, Faizal Erlangga (PT Mattawang Mediatama Solution, 2025)
This study examines the effectiveness of immersive 360° Virtual Reality (VR) as a digital medium for learning and preserving traditional dances in South Sulawesi, Indonesia. Using a mixed-methods design, the research developed and evaluated an interactive VR 360° learning module featuring five traditional dances: Tari Bosara (Bugis–Makassar), Tari To Masenga (Luwu), Tari Pakarena version Anida (Makassar), Tari Pattudu Kumba (Mandar), and Tari Pagellu (Toraja). Quantitative analysis involving 20 undergraduate students demonstrated a significant improvement in learning outcomes, with average scores increasing from 68.2 (pre-test) to 87.5 (post-test) (p < 0.01). Qualitative findings further revealed that VR enhanced learners’ cultural empathy, affective engagement, and understanding of symbolic movements and local values. Overall, the study concludes that immersive VR serves as an effective pedagogical and cultural preservation tool, bridging traditional arts with contemporary educational technology and supporting the sustainable transmission of Indonesia’s intangible cultural heritage.